An exploratory analysis of the efficacy of ocrelizumab in patients with multiple sclerosis with increased disability. Issue 1 (March 2020) - Wolinsky, Jerry S; Engmann, Natalie J; Pei, Jinglan; Pradhan, Ashish; Markowitz, Clyde; Fox, Edward J
Background: Ocrelizumab, an anti-CD20 humanized monoclonal antibody, reduced disease progression in pivotal trials of patients with relapsing (OPERA I, OPERA II) and primary progressive (ORATORIO) multiple sclerosis (MS). These effects may be particularly important among patients with increased disability. Objective: In this post hoc exploratory analysis, we evaluated the efficacy of ocrelizumab on disability progression among a subgroup of patients with MS who had increased baseline disability levels (Expanded Disability Status Scale scores ≥4.0) in the pivotal trials. Methods: During the double-blind period, patients received ocrelizumab 600 mg intravenously every 24 weeks for 96 weeks in the OPERA trials (versus interferon β-1a 44 μg subcutaneously three times per week) and for 120 weeks in ORATORIO (versus placebo). Kaplan–Meier and Cox survival analyses were used to assess disability outcome measures. Results: Baseline demographic, disease, and treatment characteristics were generally comparable across treatment groups in patients with increased disability from the OPERA and ORATORIO trials. Ocrelizumab treatment numerically, and in some instances significantly, reduced confirmed disability progression versus the comparator in these patients. Conclusions: In patients with increased baseline disability, ocrelizumab reduced the risk of confirmed disability progression versus interferon β-1a in patients with relapsing-onset MS and versus placebo in patients with progression-onset MS.